2016
DOI: 10.3991/ijep.v6i2.5683
|View full text |Cite
|
Sign up to set email alerts
|

Development of Interdisciplinary Lessons Integrating Science and Engineering in Heterogeneous Teams: Education Students’ Attitudes

Abstract: Abstract-The course "Interdisciplinary Aspects in Science and Engineering Education" is a unique course designed to expose students of science and engineering education to the characteristics of interdisciplinary teaching and learning. The theoretical part of the course deals with the nature of science and engineering and the interaction between the two, various hierarchies describing the level of integration between disciplines, and possible strategies for developing interdisciplinary lessons. In the practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The importance of STEM education is increasing in light of the growing necessity for interdisciplinary knowledge, which is essential to face the current challenges, such as brain science. In addition, the modern work today is characterized by interdisciplinary teamwork (Gero, 2016). Furthermore, the expectation is that interdisciplinary learning will contribute to the development of higher-order thinking skills (Field, Lee, & Field, 1994;Tsai, Chung, & Lou, 2017) and increase the motivation to study (Lattuca, Voight, & Fath, 2004).…”
Section: Stem Education: Definition and Objectivesmentioning
confidence: 99%
“…The importance of STEM education is increasing in light of the growing necessity for interdisciplinary knowledge, which is essential to face the current challenges, such as brain science. In addition, the modern work today is characterized by interdisciplinary teamwork (Gero, 2016). Furthermore, the expectation is that interdisciplinary learning will contribute to the development of higher-order thinking skills (Field, Lee, & Field, 1994;Tsai, Chung, & Lou, 2017) and increase the motivation to study (Lattuca, Voight, & Fath, 2004).…”
Section: Stem Education: Definition and Objectivesmentioning
confidence: 99%
“…It was instructor guidance on how to work effectively in teams that significantly changed students' satisfaction [17]. The findings of Gero [18], who examined the attitudes of heterogeneous teams of students from different backgrounds in interdisciplinary lessons, also show that from the student' perspective, the positives of teamwork significantly outweighed the difficulties associated with teamwork, with the greatest benefit being that the interdisciplinary team contributed to filling knowledge gaps. Salim et al [19] reported that students valued the learning experience of working in a team because of the opportunity to discuss the materials and exercises and to realize the extent to which they understood the topics.…”
Section: Introductionmentioning
confidence: 99%